Lying and rumination time as predictors of subclinical ketosis, metritis, and hypocalcaemia in dairy cows during the periparturient period: A systematic review and meta-analysis - Sadiq, Mohammed B.; Zaini, Syamira-Syazuana; Shaik Mossadeq, Wan Mastura; Ramanoon, Siti Zubaidah; Syed-Hussain, Sharifah Salmah (Elsevier, 2024)
The time spent lying down and ruminating are important behaviours that could be used for dairy cows’ health assessment. This systematic review and meta-analysis investigated the alterations in lying time (LT) and rumination time (RT) and their effectiveness for the detection of subclinical ketosis (SCK), metritis, and hypocalcaemia in dairy cows during the periparturient period. Each disease was subjected to meta-analysis, with the LT and RT of healthy and diseased groups, measured before and after calving. Random effects were reported for 45 trials from 19 studies and the effect size was measured as the mean difference (MD). Heterogeneity and publication bias were evaluated using the I2 statistic, and Egger’s test, respectively. Regarding SCK and metritis, the MD of LT was similar between the healthy and diseased groups in the pre-partum and post-partum (P > 0.05). Meanwhile, the MD of RT was significantly different in both periods (MD = −61.76 and −73.33 min/day, P < 0.05) for SCK and during the prepartum for metritis (MD = −23.37 min/day, P = 0.04). For hypocalcaemia, while LT only differed between the healthy and diseased cows in the post-partum, the MD of RT differed significantly between both groups in pre-partum (MD = −13.02 min/day, P < 0.001) and post-partum (MD = 21.53 min/day, P = 0.04) periods. Egger’s test for publication biases was not significant for most outcomes of interest. Meta-regression depicted a lower predicted value for MD in the LT from pasture-based cows and RT from primiparous compared to free-stalls and primiparous cows, respectively. Our findings reflect that RT is a superior behavioural attribute to LT for the early detection of SCK and hypocalcaemia during the periparturient period. Systematic assessment of RT may assist farmers to identify and categorise cows into risk groups and interventions can be performed before the onset of clinical disease.